1991
DOI: 10.2307/1938922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Algal Epiphytes on the Mussel Mytilus Californianus

Abstract: The effects of facultative epiphytes on a bivalve host were studied on an islet near Santa Catalina Island, California. The primary cover in the mid—intertidal zone was a mosaic of red algal turf (Corallina officinalis, Gigartina canaliculata, and Gelidium coulteri) and clumps of the mussel Mytilus californianus. In certain circumstances the algae attached to and overgrew the mussels. In other marine habitats, facultative epibionts benefit bivalve hosts by masking them from predators. At Catalina, spiny lobste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 46 publications
(106 reference statements)
0
24
1
Order By: Relevance
“…We hypothesize that mussel habitats might increase food abundance (1) by providing abundant substrate for sessile algal and invertebrate attachment which in turn provides increased food for herbivores and predators (Witman 1987, Young 1989, Dittman & Robles 1991, (2) by producing feces and pseudofeces which could be an attractive food source for many macroinvertebrates (Frankenberg & Smith 1967, Stuart et al 1982, similar to that demonstrated for intertidal mussels (Bayne et al 1976, Kautsky & Evans 1987, (3) by altering water flow which could allow the passive settlement of suspended particulate matter (Eckman 1983) such as detritus and planktonic larvae, and/or (4) by serving as food themselves for molluscivores, particularly crabs and gastropods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that mussel habitats might increase food abundance (1) by providing abundant substrate for sessile algal and invertebrate attachment which in turn provides increased food for herbivores and predators (Witman 1987, Young 1989, Dittman & Robles 1991, (2) by producing feces and pseudofeces which could be an attractive food source for many macroinvertebrates (Frankenberg & Smith 1967, Stuart et al 1982, similar to that demonstrated for intertidal mussels (Bayne et al 1976, Kautsky & Evans 1987, (3) by altering water flow which could allow the passive settlement of suspended particulate matter (Eckman 1983) such as detritus and planktonic larvae, and/or (4) by serving as food themselves for molluscivores, particularly crabs and gastropods.…”
Section: Discussionmentioning
confidence: 99%
“…Mussels attached to rocks, both intertidal and subtidal, also support a diverse and abundant fauna by providing refuge from predation for small individuals (Suchanek 1978, Sebens 1985, Witman 1985, food for molluscivores (Paine 1966, Menge 1976, Lubchenco & Menge 1978, Briscoe & Sebens 1988, Robles et al 1990, protection from wave induced physical forces (Suchanek 1978, Tsuchiya & Nishihira 1986, and substrate for sessile invertebrate and algal attachment (Witman 1987, Young 1989, Dittman & Robles 1991.…”
Section: Introductionmentioning
confidence: 99%
“…The larger size of C. fornicata stacks in relation to its host might be responsible for a stronger effect compared to barnacles. In addition to survival and growth, epigrowth might also negatively affect reproduction, as reported for other epifauna-basibiont associations (Dittmann & Robles 1991, Buschbaum & Reise 1999. For the C. fornicata-mussel association this remains to be investigated.…”
Section: Discussionmentioning
confidence: 91%
“…In both cases, fouling community increased the time for farmed mussel to reach the commercial size. Enright et al (1983), Dittiman & Robles (1991), Enright et al (1993), Flimlin Jr. & Mathis Jr. (1993, Claereboudt et al (1994), Lodeiros & Himmelman (1996), Taylor et al (1997), Cigarría et al (1998) also observed that fouling had reduced the weight and/or size of cultivated bivalves. However, Monteiro & Silva (1995) and Metri et al (2002), using different treatments for elimination of the fouling, did not observe significant variations in the length of the mussels with or without fouling; Freitas (1997) observed a small decrease in the size and weight of the mussels without fouling (compared to those with them), probably due to the treatment to eliminate fouling (aerial exposure).…”
Section: Discussionmentioning
confidence: 96%